Cognitive and clinical outcomes associated with cannabis use in patients with bipolar I disorder - Braga, Raphael J. (Psychiatry Res, 2012)
Studies investigating the impact of cannabis use on bipolar clinical characteristics and neurocognition are limited. The objective of the present study was to compare clinical and neurocognitive measures in individuals with bipolar disorder with a history of cannabis use disorder (CUD) versus those without a history of CUD. We conducted a retrospective analysis of a large cohort (N=200) of bipolar I subjects, either with (CUD+; N=50) or without (CUD−; N=150) a history of CUD. We compared the groups on clinical and demographic variables, as well as on performance on neurocognitive tests. Patient groups did not differ regarding age, age of onset or global assessment of functioning. Compared to the CUD− group, the CUD+ group had a higher proportion of men and a higher proportion of patients with a history of psychosis. CUD+ subjects demonstrated significantly better performance on measures of attention, processing speed, and working memory. The history of CUD is associated with history of psychosis, suggestive of poorer clinical prognosis. Interestingly, bipolar patients with history of CUD had better neurocognitive performance as compared to patients with no history of CUD.